FIBER TYPES DISTRIBUTION IN THE DIGASTRIC MUSCLE OF TUFTED CAPUCHIN MONKEY (CEBUS-APELLA) - Andreo, J. C.; Pai, V. D.; Navarro, JAC; Deoliveira, J. A. (Blackwell Wissenschafts Verlag Gmbh, 1994)
Fiber types distribution in the diagastric muscle of tufted capuchin monkey was studied by means of NADH-TR, myosin-ATPase, after alkaline and acid preincubations and SDH histochemical reactions. Three different types of fibers were found presenting an equal distribution. The percentage and types of fibers were as follow: 18.2 % SO (Slow Oxydative), 38.4 % FOG (Fast Oxydative Glycolytic) and 43.4 % FG (Fast Glycolytic). FG fibers revealed the largest area. The relatively high concentration of fast twitch (81.2 %) seems to indicate this muscle is involved with the acceleration and fast speed of jaw movements. Aerobic metabolism represented by SO + FOG fibers (56.6 %) suggests that this muscle possesses an additional role than that related to the lowering of the jaw.